Correlation of Mother's Knowledge on Stimulation With Toddler’s Gross Motor Development at The Age of 3-5 Years - Devania Angelita; Ana Yuliana; Darah Ifalahma (LPPM Universitas Duta Bangsa Surakarta, 2021)
Background: 16% of children under five in Indonesia have developmental disorders, both gross motor development and fine motor development. Approximately 35.4% developmental deviations such as deviations in gross motor skills, fine motor skills, and mental emotional deviations. In general, the purpose of preparing this scientific paper is to determine the relationship between the mother's level of knowledge about stimulation and the gross motor development of toddlers at the age of 3-5 years. Method: This type of research is analytical research with a correlation method using a cross sectional approach. The data used is quantitative data. The population in this study was 45 toddlers aged 3-5 years. Data collection techniques using questionnaires and data analysis techniques using the chi squere test. Results: The results showed that the value c2hitung of the relationship between the level of maternal knowledge about stimulation and gross motor development of toddlers aged 3-5 years was 10,230 with a significance of p = 0.006. While the value of c2tabel at the 5% significance level with df = 2 is 5.991. Because of c2hitung > c2tabel (10.230>5,991), Ho is rejected. This means that there is a significant relationship between the level of maternal knowledge about stimulation and gross motor development of toddlers aged 3-5 years. Conclusion: There is a relationship between the mother's level of knowledge about stimulation and the development of children aged 3-5 years.